2019
DOI: 10.1007/s12185-019-02651-9
|View full text |Cite
|
Sign up to set email alerts
|

Clinical update on hypomethylating agents

Abstract: Hypomethylating agents (HMAs), azacitidine and decitabine, are standards of care in higher-risk myelodysplastic syndromes and in acute myeloid leukemia patients ineligible for intensive therapy. Over the last 10 years, research efforts have sought to better understand their mechanism of action, both at the molecular and cellular level. These efforts have yet to robustly identify biomarkers for these agents. The clinical activity of HMAs in myeloid neoplasms has been firmly established now but still remains of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 98 publications
0
31
0
Order By: Relevance
“…Different types of epigenetic inhibitors are currently being applied for cancer treatment. Decitabine inhibits DNMTs, producing DNA hypomethylation (43). It is approved for treatment of haematological malignancies, such as myelodysplastic syndrome, chronic myelomonocitic leukaemia and acute myeloid leukaemia.…”
Section: Discussionmentioning
confidence: 99%
“…Different types of epigenetic inhibitors are currently being applied for cancer treatment. Decitabine inhibits DNMTs, producing DNA hypomethylation (43). It is approved for treatment of haematological malignancies, such as myelodysplastic syndrome, chronic myelomonocitic leukaemia and acute myeloid leukaemia.…”
Section: Discussionmentioning
confidence: 99%
“…The main features of MDS are myeloid cell cytopenias, morphologic dysplasia, ineffective hematopoiesis and a high risk of transformation to acute myeloid leukemia (AML) (Weinberg & Hasserjian, 2019). Although there are many new drugs for the treatment of MDS in recent years, about one-third of patients with MDS experience transformation to AML and the overall survival (OS) of MDS remains not ideal (Duchmann & Itzykson, 2019). There is accumulating evidence that MDS are associated with abnormal genetic mutations (Ogawa, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In our study, we found that the expression level of HAL was significantly correlated with the degree of gene methylation. However, as a demethylation agent, hypomethylating agent (HMA) alone has difficulty achieving the intended effect in the clinical treatment of AML (Duchmann & Itzykson, 2019). We speculated that the combination of methotrexate and HMA may achieve better efficacy when changes in HAL expression are detected.…”
Section: Discussionmentioning
confidence: 99%